An energy self-circulation system based on the wearable thermoelectric harvester for ART driver monitoring. (1st January 2023) - Chen, Jiangfan; Fang, Zheng; Azam, Ali; Wu, Xiaoping; Zhang, Zutao; Lu, Linhai; Li, Dongyang
Abstract: With the popularity and application of Autonomous-rail rapid transit in China, the status of drivers has also attracted more attention to reducing the number of accidents on complex urban roads. The previously used sensors to monitor driver status require external power, limiting the further development and application of the sensor. This paper proposes a sensor energy self-circulation system based on a copper foam heatsink using the wearable thermoelectric harvester. The proposed method consists of a thermoelectric harvester, boost circuit, and sensor module. The thermoelectric harvester module uses the wearable thermoelectric harvester to convert the waste heat of the human body into electric energy, the copper foam heatsink is used to enhance the heat dissipation capacity, and the PDMS film is used to reduce the heat loss. The DC-DC boost circuit module uses the LTC3108 to pull up the voltage to the starting voltage of the sensor and realizes power management. The sensor module uses the ultra-low-power sensor ADLX362 to detect changes in acceleration values. The experimental results show that the maximum output power of the system to the human body at a wind speed of 1.5 m/s is 145.7 μW, which can realize the self-powered applications of the proposed sensor. The result proves the feasibility of a sensor energy self-circulation system using the wearable thermoelectric harvester based on a copper foam heatsink to monitor the status of drivers. Graphical abstract: Image 1 Highlights: The proposed system can harvest human-based thermal energy for data collection. A novel energy self-circulation system is proposed for ART driver monitoring. A wearable thermoelectric harvester based on a copper foam heatsink is designed. The self-powered wearable system can effectively power low-power sensors. A maximum of 46.5 mV and 145.7 μW were recorded at a wind speed of 1.5 m/s.